Analisis Perbedaan Citra SPECT Non-AC dan CTAC pada Pemeriksaan Scintigrafi Perfusi Miokard - Nuryadin, Ridwan; Nurbaiti, Nurbaiti; Apriantoro, Nursama Heru; Budiawan, Hendra (Poltekkes Kemenkes Semarang, 2025)
Background: Myocardial Perfusion Scan displays SPECT images, which is a non invasive imaging method for a quantitative view of myocardial ischemia which can’t be done with CT myocardial perfusion. The principle of myocardial perfusion scan is that the myocardial absorption of radiopharmaceuticals is proportional to coronary heart blood flow to the myocardium. The main problem with SPECT myocardial perfusion scan imaging is photon attenuation caused by soft tissue around the heart which causes inaccurate information and attenuation artifacts. One method to reduce attenuation artifacts is hybrid CT Scan imaging with SPECT tools. CT Scan images are used to correct attenuation in SPECT images. The purpose of this research is to analyze the differences between non-AC and CTAC SPECT images which will have an impact on myocardium perfusion values on myocardial perfusion scans.Methods: This research is a quantitative analysis with a direct observation approach. The research was undertaken at Nuclear Medicine and Molecular Theranostics Installation of Dr. Hasan Sadikin General Hospital in Bandung, starting November 2023 using a SPECT CT GE NM/CT 860 gamma camera. A total of 28 patients were examined for myocardial perfusion scans. Data processing is conducted by comparing the perfusion values of myocardium on non-AC and CTAC SPECT images for 28 samples by conducting hypothesis testing using paired test sample T-Test.Result: Based on the research results, non-AC, and CTAC SPECT image data showed a normal distribution using the Shapiro-Wilk test, allowing the analysis of differences using the Paired-Samples T-test. In general, the analysis results indicate a significant difference between non-AC and CTAC SPECT images, as the sig value is less than 0.05 in the RCA and LCx vascular segments, as well as in the septal, inferior, lateral, and apical wall segments. However, no significant differences were found in the LAD vascular segment and the anterior wall segment, as the sig value is greater than 0.05.Conclusions: There are differences between non-AC and CTAC SPECT images in the RCA and LCx blood vessel segments, as well as in the septal, inferior, lateral, and apical wall segments. However, no differences are observed in the LAD blood vessel segment and the anterior wall segment.